Sistemas de impermeabilização: importância, seleção e métodos executivos - Mattevi, Bruno (2021)
Although waterproofing is a process within a construction project that plays a central role in ensuring the durability of a building, its projects and execution are not given the importance they deserve, and are often performed incorrectly and at a late stage within the construction period, generating failures and, consequently, pathologies. This work aimed to serve as a basis of information for professionals in the construction industry, in order to make them aware of the importance of having knowledge about the waterproofing process as a whole. The main waterproofing systems available on the market and their classifications, application methods, components and construction details were surveyed. In addition, the pathologies that can arise from the lack or failure of these waterproofing systems were surveyed. It was also specified and detailed some of the pertinent norms to be known by those responsible for waterproofing projects.